1997
DOI: 10.1111/j.1528-1157.1997.tb01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Kainic Acid Seizures in the Immature and Adult Brain: Ictal Manifestations and Long–Term Effects on Learning and Memory

Abstract: Summary:Purpose: While there is increasing evidence that the adverse effects of prolonged seizures are less pronounced in the immature than in the mature brain, there have been few investigations of the long-term effects of recurrent seizures during development. This study examined the effects of multiple administrations of the convulsant kainic acid (KA) on seizure characteristics and spatial learning as a function of brain development.Metho& To determine the long-term effects of serial KA seizures during ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
43
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 49 publications
5
43
0
1
Order By: Relevance
“…Enhanced hippocampal plasticity likely plays a significant role in both the memory-enhancing effects of prenatal choline supplementation (Meck & Williams, 2003;McCann et al, 2006) and its neuroprotective actions. Much like our prenatal choline supplemented adult rats, juvenile rats that experience SE also show resistance to seizure-induced hippocampal cell loss, disinhibition, and mossy fiber sprouting (Sperber et al, 1991;Haas et al, 2001), and exhibit savings in spatial learning and memory (Stafstrom et al, 1993;Sarkisian et al, 1997) when compared to adult rats that experience SE. The retention of juvenile-like neuroplasticity and response to seizures into adulthood may contribute to prenatal choline supplementation's preservation of cognitive function in the face of a neural insult.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Enhanced hippocampal plasticity likely plays a significant role in both the memory-enhancing effects of prenatal choline supplementation (Meck & Williams, 2003;McCann et al, 2006) and its neuroprotective actions. Much like our prenatal choline supplemented adult rats, juvenile rats that experience SE also show resistance to seizure-induced hippocampal cell loss, disinhibition, and mossy fiber sprouting (Sperber et al, 1991;Haas et al, 2001), and exhibit savings in spatial learning and memory (Stafstrom et al, 1993;Sarkisian et al, 1997) when compared to adult rats that experience SE. The retention of juvenile-like neuroplasticity and response to seizures into adulthood may contribute to prenatal choline supplementation's preservation of cognitive function in the face of a neural insult.…”
Section: Discussionmentioning
confidence: 84%
“…Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. accompanied by deficits in hippocampal-dependent learning and memory (Stafstrom et al, 1993;Liu et al, 1994;Sarkisian et al, 1997;Hort et al, 1999;Mikati et al, 2001). Understanding the relationship between the hippocampal response to SE and its cognitive consequences may lead to new insights into the treatment of SE and epilepsy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Is it possible that possible susceptibility to seizures leads to memory deficits in ZnT3 KO mice? Zinc deficiency is known to sensitize animals to seizure induction (Takeda et al 2003(Takeda et al , 2006 and it is also known that seizures disrupt consolidation processes (Moore et al 1993;Sarkisian et al 1997). While we cannot exclude the possibility that subseizures might occur in the mutant animals, we have never observed seizures in ZnT3 KO mice in the home cage or during any of our behavioral procedures involving electric shock in fear conditioning and testing for electric shock sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated that early-life seizures differ essentially from seizures in the adult, including the seizure behaviors, the EEG features, and their consequences. Notwithstanding the higher susceptibility to seizures, the immature brain is less vulnerable to seizure-induced injuries than the mature brain (1)(2)(3)(4)(5), and diverse conditions, such as the seizure severity, causes of seizure, or precipitating injuries may affect the long-term neurologic outcome (6 -9). In this regard, the circumstances under which a seizure in immature brain can cause permanent brain damage is of great interest (9,10).…”
mentioning
confidence: 99%